Exam Induced Stress Levels of First and Second Year Veterinary Medicine Students - Ciaramello, Taralyn M.; Lindsay, Anne; Byrnes, John J (Tufts Archival Research Center, 2019)
Thesis submitted for the MVeterinary students feel overwhelmed because they spend long days in the classroom and spend long hours in the evening memorizing excessive amounts of material for multiple choice tests. With little time for personal care or recreation, many veterinary students are believed to experience clinical levels of depression and anxiety. The purpose of this study was to pilot a peer support group intervention and measure its effectiveness in lowering depression and anxiety levels among participating subjects.S in Animals and Public Policy degree.; Keywords: veterinary medicine students, peer support group, intervention, exam induced stress, student anxiety, student depression, student stress; Thesis submitted for the MS in Animals and Public Policy degree.